The effect of a three-week multisensory training program for postural sway control (IR) - Lee, Ai Choo (2007)
Evaluating postural sway parameters can play an integral part in a rehabilitation program. One device capable of quantifying postural sway measures is the Chattecx Dynamic Balance System (CDBS). The purpose of the Study 1 was to determine the test-retest reliability and the discriminant validity of the CDBS. Forty non-injured females, ranging in age from 20 to 49 years (mean age 30.03 6.95 years) were randomly assigned according to the hours spent per week practicing sporting activities. This study demonstrated that the CDBS revealed good test-retest reliability (ICCs >0.80), but it did not have good discriminant validity in distinguishing the effect of hours spent at sporting activities per week for postural sway control between Group 1 (exercise five hours or more) and Group 2 (exercise less than five hours) when testing static and dynamic balance. Study 2 used a randomized controlled intervention to investigate whether a threeweek multisensory training program would lead to a decrease of postural sway. Twenty four non-injured young females, ranging in age from 20 to 49 years (mean age 32.17 7.70 years) and twenty four non-injured elderly females, ranging in age from 60 to 80 years (mean age 64.21 4.58 years) were randomly assigned either to training groups (i.e. young training group: YTG, and elderly training group: ETG) or control groups (i.e. young control group: YCG, and elderly control group: ECG) with no training. Before and after the training program, all four study groups were measured for overall sway (OS), medial-lateral sway (MLS), and anterior-posterior sway (APS) for six training factors using the CDBS. At posttest, the results showed significant improvement in the trained groups when compared to the untrained groups for all three postural sway measures for all six training factors in contrast with the pretest values. However, the ETG did not show significantly greater improvement when compared to the YTG. The findings also demonstrated that the trained ETG improved in their total Berg Balance Test (BBT) scores after the training program when compared to the untrained ECG. The three-week multisensory training program successfully improved postural sway control and functional balance ability for both the non-injured young and elderly females. It is recommended that when designing such programs, specific sensory systems have to be targeted in order to expect improvement (i.e. reduced sway).